2011
DOI: 10.1530/joe-10-0495
|View full text |Cite
|
Sign up to set email alerts
|

Switching of Na+, K+-ATPase isoforms by salinity and prolactin in the gill of a cichlid fish

Abstract: We identified and investigated the changes in expression of two gill Na C , K C -ATPase a-subunit isoforms (a-1a and a-1b) in relationship with salinity acclimation in a cichlid fish, Mozambique tilapia. Transfer of freshwater (FW)-acclimated fish to seawater (SW) resulted in a marked reduction in a-1a expression within 24 h and a significant increase in a-1b expression with maximum levels attained 7 days after the transfer. In contrast, transfer of SWacclimated fish to FW induced a marked increase in a-1a exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(76 citation statements)
references
References 44 publications
7
69
0
Order By: Relevance
“…It has been shown that exposing tilapia to an osmotic challenge both increases the mRNA expression of appropriate ion transporting proteins and reduces the mRNA expression of ion transporting proteins that would be maladaptive (Hiroi et al, 2005Breves et al, 2010d;Tipsmark et al, 2011;Velan et al, 2011). NKA provides the driving force for ion transport within ionocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that exposing tilapia to an osmotic challenge both increases the mRNA expression of appropriate ion transporting proteins and reduces the mRNA expression of ion transporting proteins that would be maladaptive (Hiroi et al, 2005Breves et al, 2010d;Tipsmark et al, 2011;Velan et al, 2011). NKA provides the driving force for ion transport within ionocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The electrochemical gradient that drives transmembrane ion transport is provided by the basolaterally located ion pump, Na + /K + -ATPase (NKA) (Richards et al, 2003). In tilapia, salmonids and killifish, two isoforms of NKA, α1a and α1b, are differentially expressed in the gill, according to the salinity of the habitat (Richards et al, 2003;Madsen et al, 2009;McCormick et al, 2009;Tipsmark et al, 2011;Berdan and Fuller, 2012). In tilapia, NKAα1a expression predominates in FW-acclimated fish relative to SW-acclimated fish, while NKAα1b expression has been shown to be greater or unchanged in SW-acclimated fish when compared with FW-acclimated fish .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mRNA expression of the following genes was then measured by real-time quantitative PCR: gill -atpa1a and atpa1b; liver -hsl, lepa, lepr, lipe, and lpl; and both gill and liver -glucose transporter 1 (glut1), glut4-l, and pyg. All primers, except atpa1a and atpa1b (see Tipsmark et al (2011)), were designed using ABI Primer Express (v3.0), and they are listed out in Supplementary Table 1, see section on supplementary data given at the end of this article, along with measurements of PCR efficiency calculated using the LinReg analysis of the log (fluorescence) amplification curves (Ramakers et al 2003). The mean efficiency range for all the qPCRs was 95.8-105.3%.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Transcription studies indicate that there are salinity-dependent isoforms of the α-subunit expressed in the gills of salmonids and tilapia (Richards et al, 2003;Nilsen et al, 2007;Tipsmark et al, 2011). In a recent study on Atlantic salmon parr, we used specific antibodies to characterize two NKAα1 isoform proteins, NKAα1a and NKAα1b, which are the major isoforms expressed in freshwater and seawater, respectively (McCormick et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%